Heart failure in coronary artery disease: review of medical certificates of cause of death - O. M. Drapkina; I. V. Samorodskaya; T. K. Chernyavskaya; E. P. Kakorina (Кардиоваскулярная терапия и профилактика)
The role of heart failure (HF) in mortality rates is ambiguous, and much depends on assessment criteria and accounting potential.Aim. Using medical certificates of cause of death (MCCD), to assess rates of HF, taking into account different types of coronary artery disease (CAD), sex, age and place of death.Material and methods. Data on deceased persons for 2020 were obtained from the electronic database of the Main Department of Civil Registry Office of Moscow Oblast, using the 4-digit codes of the International Classification of Diseases, Tenth Revision (ICD-10). All deaths with CAD codes (I20-25) were selected. A total of 23193 deaths were included in the analysis. The codes and verbal descriptions of complications were assessed and 3 groups were formed: without indication of heart failure (HF), with indication of HF (without chronic HF) and CHF in MCCD. Comparison of the average age of deceased, the proportion of women and men, the detection rates of certain CAD types and the place of death was carried out. Using logistic regression, the probability of chronic HF/HF as a death cause was determined, taking into account other factors.Results. Any HF was indicated in 78,9% of the MCCD (acute CAD  — 44,5%, chronic CAD — in 89,1%). Chronic HF was indicated in 27% of the MCCD (men, 30,9%; women, 22,9%; p<0,0001). The highest values were obtained in heart aneurysm — 47%; in other chronic CAD forms — slightly more than a third of the MCCD. HF was not indicated in men in 23,3% of deaths, in women — in 19%; maximum — 90% in “other acute CADs”; minimum — 11% in heart aneurysm. Average age of deceased was 73,6±12,5 years (men, 68,8±10,5; women, 78,4±12,5) (p<0,0001). In all CAD forms, the average age of deceased was significantly higher in subgroups with chronic HF than in groups with (not chronic HF) or without HF. Age, sex, CAD type, place of death (in-hospital deaths were ~2 times less common).Conclusion. According to the MCCD data, chronic HF is not the dominant complication leading to death. The results obtained require clarification in studies based on primary medical documentation.